Teacher perceptions and teaching practices of instructing students with limited eye sight in selected regular public schools of Nepal: A narrative inquiry - Padam Poudel; Dhanapati Subedi (The Open University of Sri Lanka, 2024)
Nepal's education system encourages disability inclusion, although limited eye sight students face problems in public schools. This study demonstrates limited eye sight students require qualified teachers to succeed in public schools. The primary objective of the study is to investigate the instructional approaches employed by regular instructors over an extended period of time to enhance the academic performance of children with limited eye sight. In Nepal, it is a common practice to include pupils with limited eye sight in public schools alongside their sighted peers. Therefore, students in public schools encountered several problems in classroom methodology and resources. Teachers' inclusive education practice may boost limited eye sight pupils' attendance and participation in class. A good teacher created a good learning environment, used a variety of approaches, encouraged classroom activities, addressed problems, boosted student participation, and offered other support. A qualitative Narrative inquiry was conducted to learn more about a) How do teachers in regular public schools in Nepal attempt to understand and implement inclusive education practices for limited eye sight students? This research interviewed four educators from two well known regular public schools to learn more about their perspectives on inclusive education and how they implement it in their classrooms for limited eye sight students. Social capital and Inclusive theory are used to examine public school instructors' approaches to teaching limited eye sight students. This study emphasizes the need for regular communication between teachers, students, parents, and educational stakeholders to help children with limited eye sight. Classroom inclusivity can be improved through a) teaching tactics used by teachers, b) promoting equality of opportunity and a kid-friendly learning environment, and c) removing obstacles faced by pupils.